Design of an ultrahigh‐energy‐resolution and wide‐energy‐range soft X‐ray beamline. (1st January 2014) - Xue, L.; Reininger, R.; Wu, Y.‐Q.; Zou, Y.; Xu, Z.‐M.; Shi, Y.‐B.; Dong, J.; Ding, H.; Sun, J.‐L.; Guo, F.‐Z.; Wang, Y.; Tai, R.‐Z.
<x xml:space="preserve">Abstract</x> A new ultrahigh‐energy‐resolution and wide‐energy‐range soft X‐ray beamline has been designed and is under construction at the Shanghai Synchrotron Radiation Facility. The beamline has two branches: one dedicated to angle‐resolved photoemission spectroscopy (ARPES) and the other to photoelectron emission microscopy (PEEM). The two branches share the same plane‐grating monochromator, which is equipped with four variable‐line‐spacing gratings and covers the 20–2000 eV energy range. Two elliptically polarized undulators are employed to provide photons with variable polarization, linear in every inclination and circular. The expected energy resolution is approximately 10 meV at 1000 eV with a flux of more than 3 × 1010 photons s−1 at the ARPES sample positions. The refocusing of both branches is based on Kirkpatrick–Baez pairs. The expected spot sizes when using a 10 µm exit slit are 15 µm × 5 µm (horizontal × vertical FWHM) at the ARPES station and 10 µm × 5 µm (horizontal × vertical FWHM) at the PEEM station. The use of plane optical elements upstream of the exit slit, a variable‐line‐spacing grating and a pre‐mirror in the monochromator that allows the influence of the thermal deformation to be eliminated are essential for achieving the ultrahigh‐energy resolution.